2016
DOI: 10.1080/14737175.2016.1205487
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of persistent post-concussion syndrome due to mild traumatic brain injury: current status and future directions

Abstract: Persistent post-concussion syndrome caused by mild traumatic brain injury has become a major cause of morbidity and poor quality of life. Unlike the acute care of concussion, there is no consensus for treatment of chronic symptoms. Moreover, most of the pharmacologic and non-pharmacologic treatments have failed to demonstrate significant efficacy on both the clinical symptoms as well as the pathophysiologic cascade responsible for the permanent brain injury. This article reviews the pathophysiology of PCS, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 155 publications
(100 reference statements)
0
41
0
2
Order By: Relevance
“…The minimal effective dosages of pressure and oxygen concentration are still unknown, and future studies are needed to test this issue by evaluating the optimal, case-specific dose response curves (Efrati and Ben-Jacob, 2014 ). There is a huge variability in HBO dosages (1.3–2.4 ATA) used in previous studies aimed to induce neuroplasticity in post stroke and TBI patients (Boussi-Gross et al, 2013 ; Efrati and Ben-Jacob, 2014 ; Tal et al, 2015 ; Hadanny and Efrati, 2016 ). Oxygen is not a drug and because it is mainly metabolized in the mitochondria, its pharmacodynamics varies greatly from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal effective dosages of pressure and oxygen concentration are still unknown, and future studies are needed to test this issue by evaluating the optimal, case-specific dose response curves (Efrati and Ben-Jacob, 2014 ). There is a huge variability in HBO dosages (1.3–2.4 ATA) used in previous studies aimed to induce neuroplasticity in post stroke and TBI patients (Boussi-Gross et al, 2013 ; Efrati and Ben-Jacob, 2014 ; Tal et al, 2015 ; Hadanny and Efrati, 2016 ). Oxygen is not a drug and because it is mainly metabolized in the mitochondria, its pharmacodynamics varies greatly from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed recovery has often been diagnosed as ‘post-concussion syndrome’. This label assumes the presence of common influencers of delayed recovery, but it lacks consensus criteria or clinical specificity, and subsumes varied presentations not clearly associated with the concussive injury 1 363 375–383. Since SRC is not a homogenous entity, persistent symptoms are increasingly described within specific, but often overlapping, post-concussion subtypes and should be managed as such 384…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…5,7 In addition, most treatments for mTBI, such as cognitive rehabilitation and subthreshold exercise programs, are not directed to any accompanying mental health problems. 8,9 Many studies have shown that the strongest predictors of persistent postconcussive symptoms in youth are previous mental health problems, especially depression and anxiety. 10 Additionally, previous research has shown that children from racial and ethnic minorities are less likely to receive behavioral services 11 and mental health care.…”
Section: What This Study Addsmentioning
confidence: 99%